2010
DOI: 10.1111/j.1468-0408.2010.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance Auditing and the Narrating of a New Auditee Identity

Abstract: This paper analyzes how performance auditing affects the auditee in different and sometimes unexpected ways. On the basis of a detailed case study of the Danish Ministry of Transport's encounter with performance auditing we argue that performance audit is a practice that generates multiple effects and that some of these effects can be characterized as a reconfiguration of the organizational identity of the auditee. In this process, accountabilities are reformulated and reallocated which sometimes lead to ‘blam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(87 citation statements)
references
References 34 publications
(59 reference statements)
0
86
0
1
Order By: Relevance
“…One is how the sharp audit affects the auditees. Justesen and Skærbæk () underline the blame games and feelings of discomfort among auditees, and this effect would be interesting to further investigate in connection to different audit practices and auditor roles. Another is whether there is a difference between transformations of audit in the social sector and other sectors.…”
Section: Discussionmentioning
confidence: 99%
“…One is how the sharp audit affects the auditees. Justesen and Skærbæk () underline the blame games and feelings of discomfort among auditees, and this effect would be interesting to further investigate in connection to different audit practices and auditor roles. Another is whether there is a difference between transformations of audit in the social sector and other sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have problematized the independent role of auditors as being an obstacle to impact because stakeholder involvement is associated with greater utilization (Vanlandingham 2011). Justesen and Skaerbek (2010) examined how accountability mechanisms contributed to the auditors' impact and suggested that these are forceful mechanisms in making organizations implement changes. Still they questioned whether the changes necessarily represented improvements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the accounting literature, ANT and the notion of translation has been used to emphasize how accounting devices emerge and transform (e.g., Preston, ; Lowe, ; Vikkelsø, ; and Rocher, ) and how performance auditing shapes identities (Skærbæk and Thorbjørnsen, ; and Justesen and Skærbæk, ). However, the issue of power and the construction of macro‐actors has been less developed (Czarniawska and Hernés, ).…”
Section: National Quality Registers As a Networkmentioning
confidence: 99%